Molecular analysis of the BRCA1 and BRCA2 genes in 32 breast and/or ovarian cancer Spanish familie - Osorio, Ana; Martínez, B.; Barroso, A.; Cebrián, Arancha; San Román, JM.; Lobo, F.; Robledo, M.; Benítez, Javier (Cancer Research Campaign, 2025)
It is estimated that about 5¿10% of breast cancer cases may be due to inherited predisposition. Until now, two main susceptibility genes have been identified: BRCA1 and BRCA2. The first linkage and mutational studies suggested that mutations in these two genes would account for the majority of high-risk breast cancer families, but recent studies show how the proportion of families due to BRCA1 or BRCA2 mutations strongly depends on the population and the types of family analyzed. It is now clear that, in the context of families with a modest cancer profile, which are the most commonly found in the clinical practice, the percentage of mutations found is much lower than that suggested by the first studies. In the present study, we analyze a group of 32 Spanish families, which contatined at least three cases of female breast cancer (at least one of them diagnosed before the age of 50 years), for the presence of mutations in the BRCA genes. The total proportion of mutations was low (25%), although the percentage of mutations in the BRCA1 and BRCA2 genes was higher, considering the breast and ovarian cancer families and the male breast cancer families respectively. Our results are in agreement with the idea that a great proportion of moderate-risk cancer families could be due to low penetrance susceptibility genes distinct from BRCA1 or BRCA2. © 2000 Cancer Research Campaign